Modelo de Promoção da Saúde de Nola Pender na Consulta de Enfermagem à gestante - Gama, Gabriella de Araújo (2017)
This master's thesis aimed to analyze the application of Nola Pender's Theory of Health Promotion (HPMT) in prenatal care through the nursing process. This was a qualitative study with a descriptive approach, carried out with sixteen pregnant women registered in the habitual risk prenatal care units from Family Health Strategy of the Satuba /AL City. The project was approved by the Research Ethics Committee, CAAE 54919316.0.0000.5013, and respected the ethical principles proposed in Resolution No. 466/12 of the National Health Council. Information were collected from May to December of 2016, during the pre-natal nursing visits and followed semi-structured scripts. The collected information analysis was based on the assumptions of HPMT by Nola Pender, theoretical reference adopted in this thesis. The results indicated that preponderated women in the 20-25 year age group, with adequate weight, who had completed high school, which were unemployed, which had a stable union and were in a subsequent and unplanned pregnancy. Previous behaviors that could be modified during pregnancy were predominantly related to physical activity, dietary and nutritional patterns, and exposure to tobacco compounds. The main benefits perceived by the pregnant woman for the adoption of health promoting behaviors were in relation to the fetus and the relief of pregnancy discomforts. The barriers to action were overloaded routine, malaise, and food desire. Women who believed in the ability to effect changes in their eating habits and exposure to tobacco predominated and, on the other hand, were uncertain about the prospect of change in physical activity. The final evaluation indicated that pregnant women were able to modify their habits and take on health-promoting behaviors, demonstrating that Nola Pender's HPMT is a possibility to reorient the practice of nursing care in prenatal care.